Avaliação da qualidade da assistência de enfermagem em salas públicas de vacinação de Goiânia - Mochizuki, Ludmila Bastos (2017)
INTRODUCTION: Monitoring the quality of care in vaccination rooms is essential to minimize the occurrence of post-vaccination adverse events, such as immunization error, ensuring the maintenance of confidence and adherence to immunization programs. OBJECTIVE: To evaluate the quality of nursing care in the vaccination process. METHODOLOGY: Crosssectional study in 10 vaccination rooms of a Sanitary District in the city of Goiânia. Data collection took place from July to October of 2016, using observation and interview techniques. 28 nursing professionals participated in the study, performing health care to 450 users with the preparation and administration of 736 doses of vaccines. The research was approved by the Research Ethics Committee of the Federal University of Goiás. RESULTS: The study made possible the observation of nursing care during the care of 450 users and the preparation and administration of 736 doses of vaccines. The median age of the professionals was 52.5 years. The predominant gender was female (92.8%). The medians of professional training time and performance in the vaccination ward were 24.5 and 8 years, respectively. Regarding vaccination training, 89.3% reported having gone through it in the past year. In the evaluation of the quality of nursing care, the medium score at the screening and registration stage was 54.7%, suggesting tolerable care. At the stage of preparation and administration of vaccines, the medium score was 77.9%, suggesting borderline quality of care. The nursing care provided at the Health Centers presented higher quality scores than at the Centers of Integral Health Care (60.2% versus 49.6%, p <0.001). The most frequent incidents/ immunization errors in the screening and registration stage were: lack of indication of specific vaccines for the age group (44.6%) and lack of registration of the administered vaccine in the Information System (40.3%). Regarding the incidents/ immunization errors in the preparation and administration of vaccines, the absence of hand hygiene before and / or after administration of the vaccine (93.9%), administration of the vaccine in the wrong topography (48,7%) and administration of the vaccine with inadequate needle (45,4%) were identified. In bivariate analysis, procedures with incident had lower quality scores than those without incident (77,3% versus 87,4%, p < 0,001). A total of 318 immunization incidents / errors occurred in the vaccination rooms, 166 in the screening and recording and 152 in the preparation and administration of vaccines. In the screening and registration stages, the most frequent were: absence of registration of the vaccine administered in the Information System (47.6%) and absence of indication of specific vaccines for the age group (44.6%). In the preparation and administration stages of vaccines, administration of the vaccine in the wrong topography 74 (48.7%) and administration of the vaccine with the inadequate needle 69 (45.4%). There was a high frequency of non-adherence to hand hygiene before and / or after administration of vaccines in 691 (93.9%) doses.The vaccines that showed a significant positive correlation between quality of care and administration were Pentavalente, Hepatite A, Pneumo 10, Meningo C, Tetra Viral, dTpa e Hepatite B. There was a significant negative correlation between quality of care and administration of BCG, Yellow Fever and dT. Using bivariate analysis, procedures with incidents/ immunization errors had lower quality scores than those without incidents (77.3% versus 87.4%, p <0.001). The vaccines that showed a significant positive correlation between quality of care and administration were Pentavalent, Hepatitis A, Pneumo 10, Meningo C, Viral Tetra, DTP, dTpa and Hepatitis B. There was a significant negative correlation between quality of care and administration Of BCG, yellow fever and dT. CONCLUSION: This study allowed the identification of vulnerabilities that interfere with the quality and safety of the vaccination process, indicating the need to implement measures aimed at increasing safe practices and improving nursing care in primary health care.